Fertilización asistida en mujeres de edad avanzada: ¿Quo vadis? - Rechkemmer, Adolfo F. (Revista Peruana de Ginecología y Obstetricia, 2023)
Fertilización asistida en mujeres de edad avanzada: ¿Quo vadis?